Personality-guided therapy for posttraumatic stress disorder - Everly, George S. Jr (Personality-guided psychology / series editor Theodore Millon, 2004)
(from the jacket) In Personality-Guided Therapy for Posttraumatic Stress Disorder, George S. Everly, Jr. and Jeffrey M. Lating shed light on the role personality factors play in the genesis and treatment of Post-Traumatic Stress Disorder (PTSD). With psychologically toxic events like airplane hijackings, terrorist acts, community violence, and natural disasters--an unfortunate reality in today's world--posttraumatic stress may be viewed as posing a public health challenge. Using Theodore Millon's personality-guided psychology as a framework, the authors provide insight into this challenging disorder. They discuss personality factors that can help protect against stress or increase vulnerability to stress. They explore the biological foundations of PTSD and offer practical guidance on how to assess for PTSD, how to incorporate an understanding of personality in the formation of the therapeutic alliance and in other aspects of intervention, and how to resolve trauma.